Sixteen-year dynamics of heavy metal(loid) pollution in agricultural soils of Zhejiang Province, China: Quantifying the contest between anthropogenic pressures and environmental investments - Weiwei Wang; Zhihui Fu; Linyan Xu; Jun Hu; Xiaozeng Miao; Liming Duan; Lingwen Wang; Yun Xia; Xiaohui Sun; Daohui Lin; Zhou Shi; Kun Yang (Journal of Hazardous Materials, 2026)

Simultaneous interlayer expansion and surface ion-conductive coating for high-rate graphite anodes - Liming Zhang; Gang Chen; Zhihu Wang; Changming Qu; Longfei Li; Chengyu Fu; Wenwen Deng; Baozhang Li; Yi Sun; Jia-Wei Wang; Hongfa Xiang; Xuyong Feng (Chemical Engineering Journal, 2026)

Uncertainty analysis of contaminant sources in fracture networks: A framework integrating falsification and Bayesian evidential learning - Kehan Miao; Yong Huang; Le Zhang; Liming Guo; Zhimin Fu; Thomas Hermans (Advances in Water Resources, 2026)

Kapok-fiber-supported liquid–liquid extraction enables rapid and convenient determination of five phenoxycarboxylic acid herbicide residues in beverages and oral liquids - Xinyue Wang; Jinghui Du; Jing Yang; Wenchao Han; Fengchao Wang; Zixin Zhang; Lifeng Han; Zhifei Fu; Liming Wang (Food Chemistry, 2026)

Three-dimensional suspension induction of porcine EPSCs into PGCs - Liming Yuan; Xiaolong Wu; Xiaoxiao Fu; Zuo Lei; Hongzhao Shi; Wenjie Xu; Yaya Zhao; Jiannan Li; Xueting Li; Lexi Gao; Na Li; Jinlian Hua (Theriogenology, 2026)

Preparation of amidoxime-functionalized titanium carbide and investigation of its adsorption behavior and mechanism for U(VI) - Liming Fu; Zhongchao Wang; Chao Zhou; Pengfei Yang; Guowen Peng (Process Safety and Environmental Protection, 2026)

The solubilization effects and microscopic mechanisms of a novel sugar-based Gemini surfactant for multiple DNAPLs - Yu Yao; Xueming Qin; Yufeng Fu; Yeping Gao; Hui Zhang; Chuanyu Qin; Bing Qin; Liming Ren (Journal of Hazardous Materials, 2026)

Hydrophilic anions for expanding the electrochemical stability window of water-in-salt electrolytes - Jianglin Fu; Xuzhe Li; Yubing Li; Yu Li; Ziyue Yu; Liming Lei; Shuaikai Xu; Tangming Mo; Yu Long (Chemical Engineering Journal, 2025)

Microbial metabolisms determine soil priming effect induced by organic inputs - Yingyi Fu; Wanling Liu; Zhiyi Chen; Marc Redmile-Gordon; Chao Liang; Caixian Tang; Georg Guggenberger; Shaobin Yan; Liming Yin; Jingjing Peng; Lukas Van Zwieten; Peng Wang; et al. (Soil Biology and Biochemistry, 2025)

Morphology and sulfur isotopes of pyrite in Chang73 shale: Indications for redox conditions and enrichment of organic matter and hydrocarbons - Bo Ma; Liming Ji; Qianshan Zhou; Ying Zhang; Shuang Fu; Yueye Xiao; Hao Sun (Marine and Petroleum Geology, 2025)

Unveiling DNAPLs solubilization mechanisms: How hydrophobic chain length governs characteristics in novel sugar-based Gemini surfactants - Yu Yao; Xueming Qin; Yufeng Fu; Yeping Gao; Chengwu Zhang; Hui Zhang; Chuanyu Qin; Bing Qin; Liming Ren (Journal of Hazardous Materials, 2025)

Magnetic effervescence-assisted salting-out liquid-liquid extraction enables fast and effortless determination of pyrethroid insecticide residues in fresh fruits and herbal plants - Zhifei Fu; Xinyue Wang; Jinqing You; Wenxuan Li; Lifeng Han; Liming Wang; Di Chen (Food Chemistry, 2025)

Delivery of penetration-enhancing antioxidant polyphenol nanoparticles with Codonopsis pilosula polysaccharide microneedles for synergistic treatment of psoriasis - Siqi Liu; Silu Song; Yu Zhang; Liming Yan; Yuhui Chen; Wanrong Li; Banaz Jalil; Chun Wu; Yuping Fu; Xingfu Chen; Jingyi Gu; Lixia Li; et al. (Carbohydrate Polymers, 2025)

A novel Ce-Bi2MoO6/CeVO4 Z-scheme heterojunction for peroxymonosulfate activation toward levofloxacin photodegradation - Xin Nie; Jun Li; Guohua Dong; Yong Li; Xinjia Zhang; Wenzhi Zhang; Qiu Fu; Tianyuan Xiao; Liming Bai (Journal of Environmental Chemical Engineering, 2025)

Deep Bayesian surrogate models with adaptive online sampling for ensemble-based data assimilation - Jinding Zhang; Kai Zhang; Piyang Liu; Liming Zhang; Wenhao Fu; Xu Chen; Jian Wang; Chen Liu; Yongfei Yang; Hai Sun; Jun Yao (Journal of Hydrology, 2025)

Bioenergy recovery and carbon emissions benefits of short-term bio-thermophilic pretreatment on low organic sewage sludge anaerobic digestion: A pilot-scale study - Hui Wang; Xiang Fu; Haozhe Huang; Danni Shen; Dongdong Fan; Liming Zhu; Xiaohu Dai; Bin Dong (Journal of Environmental Sciences, 2025)

Novel Optimal Staggered Grid Finite Difference Scheme Based on Gram–Schmidt Procedure for Acoustic Wave Modelling - Min Zhang; Liming Zhou; Daiguang Fu; Shiqi Dong; Haibo Wu (Pure and Applied Geophysics, 2025)

Chemical composition, odor characteristics and risk value analysis of odorants in particleboards - Fang Yang; Xianwu Zou; Liming Zhu; Bin Lv; Yuejin Fu; Bo Liu; Lina Tang; Qian Chen (Atmospheric Pollution Research, 2024)

Maternal arsenic exposure modifies associations between arsenic, folate and arsenic metabolism gene variants, and spina bifida risk: A case‒control study in Bangladesh - Chih-Fu Wei; Gwen Tindula; Sudipta Kumer Mukherjee; Xingyan Wang; Sheikh Muhammad Ekramullah; D.M. Arman; Md Joynul Islam; Mubinul Azim; Asifur Rahman; Shamantha Afreen; Md Ziaddin; Benjamin C. Warf; et al. (Environmental Research, 2024)

Blue room-temperature phosphorescent carbon dot composites with high quantum yield for information encryption and LED light emission - Shaowen Yang; Hongmei Zhang; Ke Jian; Liming Fu; Di Lan; Xihui Zhao (Chemical Engineering Journal, 2024)

Centrifugation-modulated uniform antibacterial paper with well-interconnected hierarchical pores for flexible high-sensitivity humidity monitoring - Tongtong Qin; Zhengpeng Yang; Huili Fu; Liming Zhao; Zhenzhong Yong; Li Chen; Kunjie Wu; Chenxuan Li; Chunjing Zhang; Yongyi Zhang; Yufang Cao; Hengyi Yu; et al. (Chemical Engineering Journal, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

An offline data-driven dual-surrogate framework considering prediction error for history matching - Jinding Zhang; Kai Zhang; Liming Zhang; Wensheng Zhou; Chen Liu; Piyang Liu; Wenhao Fu; Xu Chen; Ziwei Bian; Yongfei Yang; Jun Yao (Computers & Geosciences, 2024)

Chinese consumer preference for beef with geographical indications and other attributes - Rao Fu; Chenguang Li; Liming Wang; Zhifeng Gao (Meat Science, 2024)

Improved YOLOv8-Pose Algorithm for Albacore Tuna (Thunnus alalunga) Fork Length Extraction and Weight Estimation - Yuqing Liu; Zhou Fu; Liming Song; Hengshou Sui; Bin Li (Journal of Marine Science and Engineering, 2024)
Aiming at the problems of large statistical error and the poor real-time performance of catch weight in the ocean fishing tuna industry, an algorithm based on improved YOLOv8-Pose for albacore tuna (Thunnus alalunga) fork length extraction and weight estimation is proposed, with reference to the human body’s pose estimation algorithm. Firstly, a lightweight module constructed using a heavy parameterization technique is used to replace the backbone network, and secondly, a weighted bidirectional feature pyramid network BIFPN is utilized. Finally, the upper and lower jaw and tail feature points of the albacore tuna (Thunnus alalunga) were extracted using the key point detection algorithm, and the weight of the albacore tuna (Thunnus alalunga) was estimated based on the fitted relationship between fork length and weight. The experimental results show that the improved YOLOv8-Pose algorithm reduces the number of model parameters by 13.63% and the number of floating-point operations by 14.03% compared with the baseline model without decreasing the accuracy of the target detection and key point detection and improves the model inference speed by 374%. At the same time, it reduces the drift of the key point detection, and the error of the comparison with the actual albacore tuna (Thunnus alalunga) body weight is not more than 10%. The improved key point detection algorithm has high detection accuracy and inference speed, which provides accurate yield data for pelagic fishing and is expected to solve the existing statistical problems and improve the accuracy and real-time performance of data in the fishing industry.

Long-term cold storage of platelets for transfusion based on zwitterionic magnetic microgels - Yihao Fu; Yiming Ma; Yunqing Tian; Liming Zhang; Jing Yang; Lei Zhang (Chemical Engineering Journal, 2024)

Use of model substitution in the inversion of dispersion curves in weak subsurface layers - Daiguang Fu; Shuangxi Zhang; Mengkui Li; Liming Zhou; Min Zhang (Journal of Applied Geophysics, 2024)

Facilitating photogenerated carrier transfer and water oxidation kinetics of BiVO4 photoanode via novel Zn@Co3C functional layer - Weibing Li; Liming Wang; Jie Zhou; Ning Wang; Xinyang Fu; Yibo Wang; Yuyu Bu; Yaping Zhang; Lei Wang (Chemical Engineering Journal, 2023)

Effects of stand age and structure on root distribution and root water uptake in fast-growing poplar plantations - Wei Zhu; Ou Zhou; Yiming Sun; Ximeng Li; Nan Di; Doudou Li; Gulimire Yilihamu; Yafei Wang; Jingyi Fu; Benye Xi; Liming Jia (Journal of Hydrology, 2023)

Automatic skin lesion classification using a new densely connected convolutional network with an SF module - Pufang Shan; Chong Fu; Liming Dai; Tihui Jia; Ming Tie; Jun Liu (Medical & Biological Engineering & Computing, 2022)

Evaluation and improvement of the greenness of plasma spraying through life cycle assessment and grey relational analysis - Jing Liu; Liming Wang; Fangyi Li; Yanle Li; Xueju Ran; Lin Kong; Yan Fu (The International Journal of Life Cycle Assessment, 2021)

Prediction of Biodegradability for Polycyclic Aromatic Hydrocarbons Using Various In Silico Modeling Methods - Gong Cheng; Liming Sun; Jie Fu (Archives of Environmental Contamination and Toxicology, 2018)

Assessing the impacts of the changes in farming systems on food security and environmental sustainability of a Chinese rural region under different policy scenarios: an agent-based model - Chengcheng Yuan; Liming Liu; Xiaoxing Qi; Yonghu Fu; Jinwei Ye (Environmental Monitoring and Assessment, 2017)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Changes in cloudiness over the Amazon rainforests during the last two decades: diagnostic and potential causes - Paola A. Arias; Rong Fu; Carlos D. Hoyos; Wenhong Li; Liming Zhou (Climate Dynamics, 2011)